Reacción psicológica ante la experiencia de abuso sexual extrafamiliar en padres de niños abusados (2018)
ABSTRACT: This paper is the result of a research whose objective was to analyze psychological reactions in parents of children who have suffered extra-familial sexual abuse, ASE; this research was conducted at Centro de Atención Integral a Víctimas de Abuso Sexual – CAIVAS – Prosecutor office, in Medellin, Colombia.